Empreendedorismo “inovador” nas escolas estaduais de educação profissional no contexto da crise estrutural do capital - Goes, Glória Maria Vasconcelos (2021)
Given the structural crisis of capital, entrepreneurship arises as the “solution” to unemployment, putting in the worker the responsibility for creating their own means to supply their basic needs, in a world seen as naturally competitive. The entrepreneurial society presupposes knowing how to live with the risk, pursue innovation, stimulate creativity and fight between the best ones. The psychological characteristics of entrepreneurs (exacerbated motivation, leadership, initiative etc.) were once considered inherent, can now be transmitted through education, especially professional education, aiming to form the entrepreneur individual in a context of productive capital restructuring. This entrepreneur assumes the role of entrepreneur, when makes a business (first mode), or intrapreneur, when is an employee / civil servant, for those who remain in employment (second mode), or be a social entrepreneur, who along with other entrepreneurs, they need to achieve social cohesion (third mode). Thus, the aim of this study is to analyze the effects of structural adjustment in the capital in Brazilian professional education, particularly in Schools of Professional Education of the state network of Ceará, under the rule of innovative entrepreneurship. To realize this objective we will seek: 1) To analyze the new conformations of entrepreneurship in the context of structural capital crisis; 2) To reflect on the effects of the restructuring process in professional education; 3) To analyze the inclusion of entrepreneurship discourse in basic documents in Schools of Professional Education from Ceará. In the investigative path of quantitative and qualitative character, we adopted bibliographical and documentary research in the light of historical and dialectical materialism. Our critical analysis points out that the introduction of entrepreneurial culture, strengthen public-private partnership in the context of the State's counter-reform, in which the entrepreneur and the entrepreneurial State are together, engender the great and necessary social dialogue to prevent the ruin of capitalism. The education focused on “learning how to make entrepreneurship” gains expression in State Schools of Professional Education, with a focus on behavioral skills. It intends to put in the minds workers’ children the necessary creation of survival strategies, by the risk management and by themselves. The “effective” management of risk would allow workers to develop their resilience, facing the difficulties proactively, in a context where the uncertainty and chaos are naturalized. In the context of deepening social inequalities, as a result of a capitalist sociability, the task of fake democratic governments, is towards encouraging civic attitudes and deny the real conflict that underlies the model based on private ownership of means of production. The task of education, particularly professional education, is to form the unilateral entrepreneurial man, reinforce the dichotomy between capital and work, in the knowledge society, disseminating the culture of peace and union among unequal individuals to control the uncontrollable capitalist sociability in structural crisis.